Deployment of stent grafts in curved aneurysmal arteries: toward a predictive numerical tool. (January 2015) - Perrin, David; Demanget, Nicolas; Badel, Pierre; Avril, Stéphane; Orgéas, Laurent; Geindreau, Christian; Albertini, Jean‐Noël
Summary The mechanical behavior of aortic stent grafts plays an important role in the success of endovascular surgery for aneurysms. In this study, finite element analysis was carried out to simulate the expansion of five marketed stent graft iliac limbs and to evaluate quantitatively their mechanical performances. The deployment was modeled in a simplified manner according to the following steps: (i) stent graft crimping and insertion in the delivery sheath, (ii) removal of the sheath and stent graft deployment in the aneurysm, and (iii) application of arterial pressure. In the most curved aneurysm and for some devices, a decrease of stent graft cross‐sectional area up to 57% was found at the location of some kinks. Apposition defects onto the arterial wall were also clearly evidenced and quantified. Aneurysm inner curve presented significantly more apposition defects than outer curve. The feasibility of finite element analysis to simulate deployment of marketed stent grafts in curved aneurysm models was demonstrated. The study of the influence of aneurysm tortuosity on stent graft mechanical behavior shows that increasing vessel curvature leads to stent graft kinks and inadequate apposition against the arterial wall. Such simulation approach opens a very promising way toward surgical planning tools able to predict intra and/or post‐operative short‐term stent graft complications. Copyright © 2015 John Wiley & Sons, Ltd.